Governance Exploration: Municipal Control in Nepalese School Education (Siddhajyoti Interdisciplinary Journal, 2025)
The implementation of the National Education Policy 2018 in Nepal has shifted school governance to municipal authorities including Ward Chair into School Management Committees. In this context, the study examines the impact of the changed education policy using a convergent parallel mixed-method research. The study used "management and leadership theories" connecting to school governance theories and their implication. The information was collected through interviews with principals and teachers, and surveys from 130 teachers including head teachers across 26 schools. The information sought from interviews and survey method have been interpreted and analysed thematically and statistically. The study revealed that while resource allocation improves, the significant dissatisfaction exists in governance. The municipal representatives lack the educational management expertise necessary for effective school leadership, resulting in strategic and operational gaps. The study recommends for training on leadership and management for the collaborative and effective school governance and to improve educational outcomes.